2022
DOI: 10.1088/1742-6596/2157/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

High order thinking skills: can it arise when a prospective teacher solves a controversial mathematics problem?

Abstract: High order thinking skills are important for prospective mathematics teachers. This study aims to describe whether High Order Thinking Skills (HOTS) can appear when prospective teachers solve controversial math problems. This research has been conducted using descriptive qualitative research. The instruments that have been used are controversial math test questions and interviews. The research subjects used were 150 prospective mathematics teachers, and three people who experienced controversy were taken to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…The findings in this study are the stages of reasoning that have been described by Rosyadi et al (2022) and can be used in other relevant studies. In making conjectures and evidence, prospective teachers have not found the right pattern (Ulger 2018).…”
Section: Making Conjectures and Evidencementioning
confidence: 53%
“…The findings in this study are the stages of reasoning that have been described by Rosyadi et al (2022) and can be used in other relevant studies. In making conjectures and evidence, prospective teachers have not found the right pattern (Ulger 2018).…”
Section: Making Conjectures and Evidencementioning
confidence: 53%
“…Di dalam persepsi terdapat proses penyerapan, pemahaman dan penilaian (Mania & Alam, 2021;Margot & Kettler, 2019;Rashid et al, 2021). Berdasarkan hasil penelitian (Rosyadi, 2022), diperoleh informasi bahwa calon guru dalam menyelesaikan masalah kontroversial, melalui proses analisis masalah yang diberikan, menyelidiki, dan melakukan pengecekan dari yang sudah dituliskan.…”
Section: | Pendahuluanunclassified
“…Meanwhile, Subanji et al (2021) suggested the level of reasoning to solve mathematical problems. In addition, Rosyadi et al (2022) revealed the link between controversial problem solving and critical thinking using HOTS (higher-order thinking skills). Based on those previous studies, there has been limited research linking controversial mathematical problems with metacognitive strategies.…”
Section: Introductionmentioning
confidence: 99%